2012
DOI: 10.3844/ajassp.2012.807.817
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation on Antibacterial Activity of <i>Lactobacillus acidophilus</i> Strains Isolated from Honey

Abstract: Problem statement:This study reports the isolation of lactic acid bacteria from 13 honey samples produced in Malaysia, Libya and Saudi Arabia and their antibacterial activity against three Gram negative pathogenic bacteria. Approach: A modified MRS agar with 0.8% CaCO 3 and MRS with 1% glucose was found to facilitate isolation of LAB compared to MRS, tomato juice agar and modified tomato juice agar. 32 isolates were confirmed LAB by catalase test and Gram staining. Six isolates were screened for antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 34 publications
1
44
0
2
Order By: Relevance
“…Generally, LAB species may differ from place to place. Hosny et al, (2009) Aween et al, (2012). Lactobacillus is commonly associated with honey bees even in India (Pattabhiramaiah et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, LAB species may differ from place to place. Hosny et al, (2009) Aween et al, (2012). Lactobacillus is commonly associated with honey bees even in India (Pattabhiramaiah et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Calcium carbonate (CaCO 3 ) was added to MRS medium to induce more LAB growth (Aween et al, 2012). Cycloheximide was added to the above medium to avoid fungal contamination.…”
Section: Isolation and Enumeration Of Labmentioning
confidence: 99%
“…The S. aureus used in this study demonstrated low MAR index 11% compared E. coli and P. aeruginosa with 55 and 66%, respectively. S. Typhimurium and B. subtilis showed highest MAR index (88%) compared to other tested bacteria.Similarly, multiple antibiotic resistant bacteria was shown by several tested pathogens including S. Typhimurium ATCC13311 that was resistant to 10 antibiotics especially to bacitracin, cephalothin, penicillin G, vancomycin and strepromycin; E. coli ATCC25922 was resistant to bacitracin, penicillin G and vancomycin observed by Aween et al (2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Propolis of Malaysian honey inhibited the growth of Staphylococcus aureus and Escherichia coli as reported by Rahman et al (2010). Honey of Malaysia, Libya, New Zealand and Saud Arabia contain lactic acid bacteria with antibacterial activity against selected Multiple Antibiotic Resistant (MAR) Gram-positive bacteria and Gram-negative bacteria (Aween et al, 2012a;2012b).…”
Section: Ajasmentioning
confidence: 99%
See 1 more Smart Citation